Novel glycoconjugated squaraine dyes for selective optical imaging of cancer cells. Issue 39 (2nd May 2017) - Shimi, M.; Sankar, Vandana; Rahim, M. K. Abdul; Nitha, P. R.; Das, Suresh; Radhakrishnan, K. V.; Raghu, K. G.
Abstract : Glycoconjugated squaraine dyes for selective internalisation in cancer cell lines are reported. The cancer cell selectivity was achieved through the "Warburg effect". Abstract : Novel glycoconjugated squaraine dyes were synthesized, which exhibited excellent internalization in tumor cells and are potent fluorogenic imaging probes for tumor selective optical imaging.